The effect of body mass index on quality of life in modified single stoma cutaneous ureterostomy or ileal conduit after radical cystectomy - Wan‐Jin Zhang; Xu‐Yun Huang; Bin Lin; Wen‐Cai Zheng; Zhi‐Bin Ke; Xiao‐Dan Lin; Jia‐Yin Chen; Hai Cai; Yun‐Zhi Lin; Ye‐Hui Chen; Qing‐Shui Zheng; Yong Wei; et al. (Cancer Medicine, 2023)
Abstract Objective To explore the influence of postoperative body mass index (BMI) change on postoperative quality of life (QOL) in patients undergoing radical cystectomy (RC) plus modified single stoma cutaneous ureterostomy (MSSCU) or ileal conduit (IC). Methods Patients were divided into two groups according to different BMI change patterns: patients experiencing an elevated postoperative BMI level, along with a clinically significant increase in their BMI (an increase of more than 10%) were categorized as Group 1, while patients experiencing a decrease postoperative BMI level, along with a clinically significant reduction in their BMI (a decrease of more than 5%) were categorized as Group 2. Spearman correlation analysis was used to examine the correlations between quality‐of‐life scores and postoperative clinical parameters. Results Spearman correlation analysis showed that postoperative BMI, late complications and catheter‐free state were significantly associated with postoperative global QoL and symptom scale in MSSCU and postoperative global QoL and physical scale in IC patients. Additionally, postoperative BMI, catheter‐free state and the use of adjuvant therapy were associated with bad performance in many scales of QoL like body image, future perspective, social scale, future perspective (MSSCU), and abdominal bloating (IC) (Table 2, p<0.05). Patients in Group 2 with significant weight loss had a better Global QoL, a lower rate of stomal stricture and a higher catheter‐free state compared with those in Group 1 in both IC and MSSCU patients. MSSCU patients in Group 2 could achieve a comparable Global QoL as to IC patients in Group 1. Conclusion Controlling the substantial increase in body weight after surgery contributes to improving QoL, reducing the occurrence of stomal stricture, and ensuring a postoperative catheter‐free state in BCa patients undergoing MSSCU.